2018
DOI: 10.3390/jcdd5040054
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics in Cardiac Development

Abstract: The beating heart is subject to intrinsic mechanical factors, exerted by contraction of the myocardium (stretch and strain) and fluid forces of the enclosed blood (wall shear stress). The earliest contractions of the heart occur already in the 10-somite stage in the tubular as yet unsegmented heart. With development, the looping heart becomes asymmetric providing varying diameters and curvatures resulting in unequal flow profiles. These flow profiles exert various wall shear stresses and as a consequence diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 110 publications
0
29
0
Order By: Relevance
“…Heterospecific interactions between a small number of the transcription factors Tbx5 and Nkx2.5, and GATA4, also part of the cardiogenic tool kit, underlying gene expression patterns in specific tissues, have been demonstrated in mammalian cardiogenesis . However, this shows much complexity and requires fine‐tuning involving additional partners, including histone modifications, epigenetic regulation, involvement of hemodynamics, regulation of cell movement, and participation of microRNAs to provide for expansion of cardiac progenitors, compartments, and cell differentiation.…”
Section: The Second Heart Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterospecific interactions between a small number of the transcription factors Tbx5 and Nkx2.5, and GATA4, also part of the cardiogenic tool kit, underlying gene expression patterns in specific tissues, have been demonstrated in mammalian cardiogenesis . However, this shows much complexity and requires fine‐tuning involving additional partners, including histone modifications, epigenetic regulation, involvement of hemodynamics, regulation of cell movement, and participation of microRNAs to provide for expansion of cardiac progenitors, compartments, and cell differentiation.…”
Section: The Second Heart Fieldmentioning
confidence: 99%
“…Each individual cushion probably receives its own balanced set of mesenchymal cells . In chicken embryos, it is shown that the formation of the semilunar valves highly depends on the interaction of endocardial and NC‐derived mesenchymal cells guided by hemodynamical forces sculpting the OFT . It is noteworthy that also in these events of cardiogenesis, asymmetric development is apparent, although the main leaflets of the aortic and pulmonary semilunar valves originate from the same two OFT endocardial cushions.…”
Section: The Oft Endocardial Cushionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphogenetic processes underlying the differences in the structure of the elastic arteries [5] and the muscular arteries are still poorly understood. Most probably, these are the results of origin of the endothelial and the VSMC populations in combination with the role of hemodynamics [7]. The great arteries in general are more influenced by high shear stress and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed in order to discover the genetic and molecular signaling pathways involved in EndMT, e.g., [18,19,20,21,22]. Several studies have also pointed to flow-mediated signaling pathways as key drivers of EndMT, e.g., [23,24,25,26,27,28,29,30]. In particular, altered hemodynamics are known to cause congenital heart defects, and it is therefore desirable to understand in more detail how perturbations in flow affect EndMT such that valve and septa formation are disrupted.…”
Section: Introductionmentioning
confidence: 99%